Hubungan Kausalitas antara Deforestasi, Pertanian dan Pertumbuhan Ekonomi: Studi Empiris di Indonesia - Maksimilianus Paulus Jati Gamatara; Marianus Antonius Deo Datus Banase; Adelheid Elisabet Loda (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2025)
This study aims to thoroughly explore the direction of the relationship formed, both short-term and long-term relationships, as well as to find out whether the relationship is one-way or two-way and the complex interactions between deforestation, agriculture, and economic growth (tripartite relationship analysis) in Indonesia. The analysis model used is the Vector Error Correction Model (VECM) on time-series data from 1991 to 2023. This study reveals the dynamic interactions between the three variables. The estimation results show that in the short term, deforestation and agriculture, as well as Gross Domestic Product (GDP) per capita and agriculture, have a mutually influential relationship, while GDP per capita and deforestation only have a one-way relationship, namely GDP per capita influences deforestation. However, in the long term, there is a causal relationship or a mutually influential relationship between the three variables. These findings emphasize the importance of an economic development approach that considers environmental sustainability and efficient land use.